Between state conditioning and rereading in critical crime: a possible debate over the revision of the methodological frameworks in Latin American criticism - Juan Martín Salandro (Universidad Nacional de Mar del Plata, 2021)
In the following paper, we propose to analysing the different possibilities of making a literary, or cultural, critique, related to the concept of “crime”. For this, we will take notions such as “language empire” and “crime”, given by the argentinian author Josefina Ludmer (1939-2016). Therefore, two instances are presented to relate the critical view with the society´s; in first place, conditioning, understood as a State´s action as prefigurator, througth the symbolic violence, of the representation ways. Secondly, the re-reading claimed by the author about/ against the inherited theoric legacy. Here is where we propouse the concept of “critical crime”. It has to be taken into account that our purpose is not focused on analysing the author´s theoric corpus, instead, using it to start formulating an own concept about literary criticism practise and it´s epistemological models. Due to this idea, we will use the reference of different methodological problems and authors, relating them all in one network, where Josefina Ludmer could be located on the center.